Perspectives on Physical Education and Sports Management Academic - Carmen I. RĂCHITĂ (Revista de Management Comparat International)
University physical education should be recognized as an indispensable component in shaping the young generation. University physical education represents a fundamental psycho-behavioral dimension of the personality characteristics for students in medicine. The relation between physical education and the personality characteristics of the students in the medical field is the prospect of a scientific research which should function in order to deepen the process of knowledge of this problem while concomitantly with the amplification of the studies of transposition in life, of the results of the scientific investigation. The project wishes to highlight the possibilities of action on the personality characteristics of the students in medicine through the systematic and conscious practice of physical exercises. The knowledge of the psychological profile and the efficient acting on the personality characteristics of the students will have positive bio-psycho-socio-professional implications.